Patrones de resistencia bacteriana en bacilos no fermentadores aislados de pacientes de la clínica Medilab-Medihospital, Loja, 2018-2020 - Guamán Quizhpe, Amy Gisella (2022)
Bacterial resistance in non-fermenting bacilli constitutes a global threat to the health system, especially in the hospital environment due to its multi-resistance to antimicrobials; these microorganisms are the cause of most nosocomial infections, with limited therapeutic options in infections caused by Pseudomonas aeruginosa, Acinetobacter baumannii and Stenotrophomonas maltophilia, considered as bacteria subject to critical priority surveillance. The present study of quantitative approach and a retrospective-cross-sectional design aimed at determine the patterns of bacterial resistance in non-fermenting bacilli isolated from patients who attended to the clinic Medilab-Medilhospital, Loja 2018-2020. The results obtained showed that P. aeruginosa was isolated mainly from the outpatient service (59 %) and according to the type of urine sample (27 %); A. baumannii strains presented a 100% resistance profile to ampicillin sulbactam; According to the isolates in pre-pandemic and prepandemic period, there was a connotation in both periods where A. baumannii during the pandemic decreased the profile of resistance to ampicillin-sulbactam, ceftazidime and gentamicin, while Acinetobacter spp. increased the resistance profile to more than 70% to cefepime, ceftazidime, ceftriaxone, ciprofloxacin and gentamicin; no records of resistance by Extended Spectrum Beta-lactamase (ESBL) or caused by carbapenemase enzymes were found, although resistance to carbapenems is denoted by other resistance mechanisms